UNIFICATION OF BOOSTERS DEVICES STANDS FOR TESTING OF TRACTION MOTORS OF ELECTRIC LOCOMOTIVES DC - Loza, P. O. (Science and Transport Progress, 2009)
The methods of determination of the optimal parametric series of boosters for the test desks for traction electric motors of direct current electric locomotives are offered in the article.